KORELASI PARAMETER KUALITAS AIR DAN PRODUKTIVITAS UDANG VANAME (Litopenaeus vannamei) DALAM SISTEM KOLAM HDPE - Adianto, Asep; Nirmala, Kukuh; Hastuti, Yuni Puji; Supriyono, Eddy (JARI : Jurnal Akuakultur Rawa Indonesia, 2024)
Vannamei shrimp remains one of the leading fisheries commodities in Indonesia. This study aims to analyze the correlation between measured parameters and identify the most influential water quality parameters affecting the productivity of vannamei shrimp reared in HDPE pond systems. This non-experimental research was conducted by directly sampling from a shrimp pond in Patrol, Indramayu, over a 49-day cultivation period. The measured data included water quality parameters (physical, chemical, and biological) and shrimp growth performance parameters (survival rate, feed conversion ratio, average body weight, and average daily gain). Measurements were carried out both in the field and in the laboratory. The results showed that several water quality parameters exceeded their optimal thresholds (e.g., hardness levels reached 7,000 mL⁻¹ in pond D3). However, growth performance parameters still indicated relatively high values. Based on survival rate calculations, pond D2 had the highest Survival Rate (96%), while pond C3 recorded the lowest (67%). These findings suggest that water quality parameters collectively support shrimp growth despite some of them being outside the ideal range. Total Organic Matter (TOM) and Dissolved Oxygen (DO) were identified as the most influential water quality parameters for shrimp productivity.